5-year retrospective evaluation of direct composite restorations in orthodontically treated patients. (January 2021) - Comba, A.; Vergano, E.A.; Baldi, A.; Alovisi, M.; Pasqualini, D.; Castroflorio, T.; Stura, I.; Migliaretti, G.; Berutti, E.; Scotti, N.
Abstract: Objectives: In patients affected by dimensional discrepancy between size of anterior maxillary and mandibular teeth, orthodontic therapy could be necessary to solve occlusal problems. However, anterior restorations are indicated to finalize the aesthetic aspect of the therapy. The aim of the present retrospective clinical study was to evaluate the long-term outcomes of direct additive composite restorations performed to correct anterior teeth discrepancies persisting after orthodontic treatment. Methods: Patients with dimensional teeth discrepancy, subjected to a combined orthodontic-restorative treatment, between January 2009 and January 2019, were recalled for the present retrospective evaluation and divided in two groups according to the restoration performed: G1) diastema closure; G2) tooth shape modification. All patients, after ortho therapy, were subjected to a standardized restorative rehabilitation of the anterior area. All restorations were performed by a single experienced operator employing the same materials. During recall visits, two calibrated examiners evaluated the restorations and recorded USPHS data. Kaplan-Meier estimator and Cox-regression analysis were performed. Statistical significance was set for p < 0.05. Results: 53 patient were included, with a total of 169 restoration (G1:110;G2:59). The mean study time period was 5 year (ranging from 6 month to 10 years). The overall survival rate of additive restoration was 2, 59% (G1:2, 07%; G2:0, 47 p < 0.05). Chipping of the material was the most frequent adverse event (G1:13, 64%; G2:1, 69), followed by composite wear (G1:9, 09%; G2:5, 17). Conclusions: Based on the obtained results, good clinical performances were shown at a 5-year interval. A low number of failures were collected and most of them were classified as reparable. Only few cases needed complete reintervention. Clinical Significance: Showing that a direct approach in restoring anterior teeth for diastema closure or shape modification is a valid alternative in terms of durability and aesthetics to more invasive procedure such as indirect restorations